Basic researchEffect of dietary omega-3 fatty acid deficiency on heart rate variability in hooded rats - Weisinger, Harrison S.; Salem Jr, Norman; Makino, Kevin K.; Hibbeln, Joseph R.; Sinclair, Andrew J.; Weisinger, Richard S.; DePetrillo, Paolo B. (Archives of Medical Science, 2007)
Introduction: Recent reports in adult humans suggest that heart rate variability is modulated by the concentration of omega-3 polyunsaturated fatty acids (PUFA) contained in blood cell membranes. Material and methods: Hurst analysis of ECG data was conducted on 12 male adult hooded (Long-Evans) rats, representing the 3rd generation to be fed diets that were either deficient in, or supplemented with, omega-3 PUFA. ECG data were obtained from surface electrodes and 4000 beats were analyzed for each animal. Results: Dietary manipulation, despite leading to large changes in tissue omega-3 PUFA levels, did not significantly affect the complexity of heart rate dynamics, with Hurst exponent (H) values of 0.15±0.02 and 0.12±0.03, for animals fed omega-3 fatty acid-adequate and -deficient diets, respectively. Mean heart rate was also unaffected by the diets. A power calculation revealed that about one hundred animals per group would have been required to avoid a type II error. Conclusions: According to this model of dietary PUFA manipulation, omega-3 fatty acids are unlikely to exert a large effect on the autonomic functions that control heart rate variability. Prospective studies into the effect of omega-3 fatty acids on HRV should consider the need for large sample size as estimated by the results contained in this report.